Vehicle Yaw Rate Control Based on Fuzzy PID Control Technology - Ahmed, Abdussalam Ali; Abunada, Alaa R. H. (Journal of Advanced Research in Mechanical Engineering and Technology, 2019)
In this paper, control of vehicle yaw stability system is studied by using a two vehicle models where the first one is a linear two degree of freedom vehicle model to design the controller and the other one is a planar motion model which represents a nonlinear vehicle model (actual vehicle). The strategy of vehicle yaw stability control based on the yaw rate control which adopts the fuzzy PID controller. Compared to traditional PID control, the fuzzy PID control can adjust and tune the proportional, integral and derivative parameters and make efficient the system responds. To make sure that Fuzzy PID controller works well, it will be tested at two cases of input steering angle of the vehicle front tires which are a step signal maneuver and a single-lane-change maneuver. Various of computer simulations and results show that the control system of vehicle yaw stability and using of fuzzy PID controller can improve the stability and handling of vehicle significantly.